Bridging the Knowledge Gap Between Environmental Ethics and Microplastic Pollution: An Interdisciplinary Approach to Sustainability - Galuh Ajeng Rahmadhani; Retno Widowati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The knowledge gap between environmental ethics and the reality of microplastic pollution is examined through an interdisciplinary approach. Microplastic pollution has become a persistent and widespread environmental contaminant, with more than 170 trillion plastic particles estimated to be floating in the world's oceans. Recent studies show that microplastics have been detected in human blood, drinking water, and the global food chain. However, public awareness and policy responses remain behind the severity of the problem. Microplastic pollution is analyzed from ecological, toxicological, and social perspectives, while gaps in the understanding and implementation of environmental ethics are identified. Interdisciplinary approaches integrating natural sciences, social sciences, humanities, and technology are also evaluated. The findings indicate that effective solutions require systemic transformation, including technological innovation, policy reform, a shift toward a circular economy, and changes in public behavior. Recommendations include strengthening interdisciplinary research with more standardized methodologies, implementing evidence-based regulation guided by the precautionary principle, adopting circular economy and extended producer responsibility schemes, and improving environmental education and public literacy. The conclusion emphasizes the urgency of collective action informed by scientific evidence and guided by ethical principles to achieve genuine environmental sustainability.